Alkylation of Arylsulfonyl Cyanides To Form Alkyl Sulfones - Sommer, Ava G.; Tung, Pinku; Mankad, Neal P. (Synthesis, 2025)
Arylsulfonyl cyanides, such as commercially available TsCN, undergo base-mediated C–S coupling with alkyl halides to provide alkyl sulfones. A wide range of alkyl halides with diverse functionalities were found to react with moderate to high efficiency. Based on experimental observations, it is proposed that the arylsulfonyl cyanides react with the base to in situ generate arylsulfinates, which then act as SN2 nucleophiles towards the alkyl halides. A major advantage of this method is that it circumvents the problem of metal sulfinate nucleophiles having low solubility, by using soluble arylsulfonyl cyanides as soluble pro-nucleophiles.
Keywords: alkyl sulfones; sulfonyl cyanides; C–S coupling; arylsulfinates; substitution